PENGARUH PENERAPAN METODE QUANTUM LEARNING TERHADAP HASIL BELAJAR MATA PELAJARAN BAHASA INGGRIS - S., Dwi Martine (JIV-Jurnal Ilmiah Visi, 2010)
The purpose of this study is to find out the effects of quantum learning method to the learning achievement in English subject for the learning participants at the Community Learning Activities Center in Pisangan Lama area, East Jakarta. The study was conducted at Miftahul Jannah Community Learning Activities Center, Pisangan Lama, East Jakarta, for one semester, from August to December 2008. It observed the effects in cognitive, affective, psychomotor aspects to the learning participants of Package C. The method employed was experiment in which the researcher was directly involved. The data were collected from 40 Package C participants randomly selected as the samples out of 70 participants of Grade III. The experiment proved that there are significant effects of quantum learning method to the learning achievement in English subject for the learning participants at Miftahul Jannah Community Learning Activities Center, East Jakarta.